2004
DOI: 10.1111/j.0904-2512.2004.00097.x
|View full text |Cite
|
Sign up to set email alerts
|

Utility of urinary pyridinoline and deoxypyridinoline ratio for diagnosis of osteoarthritis at temporomandibular joint

Abstract: These findings suggest that the level of Pyr and the Pyr/Dpyr ratio in urine may be a useful diagnostic indicator for intra-articular pathologic changes during TMJ OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
(33 reference statements)
1
9
1
1
Order By: Relevance
“…Assays on urine samples have shown elevated levels of pyridinoline (Pyr) and deoxypyridinoline (Dpyr) collagen cross-links, which are known markers of bone and cartilage turnover, in patients with osteoarthritis of the TMJ. 87 Additionally, elevated amino acid secretion products were found in the urine of patients with chronic muscle pain TMD. 88 Similarly, preliminary studies using serum have suggested increased estrogen levels 53,89 in TMD patients and increased levels of interleukin-1beta and C-reactive protein in arthritic TMJ diseases.…”
Section: Biomedical Approaches To Diagnose Alleviate or Prevent Joimentioning
confidence: 99%
“…Assays on urine samples have shown elevated levels of pyridinoline (Pyr) and deoxypyridinoline (Dpyr) collagen cross-links, which are known markers of bone and cartilage turnover, in patients with osteoarthritis of the TMJ. 87 Additionally, elevated amino acid secretion products were found in the urine of patients with chronic muscle pain TMD. 88 Similarly, preliminary studies using serum have suggested increased estrogen levels 53,89 in TMD patients and increased levels of interleukin-1beta and C-reactive protein in arthritic TMJ diseases.…”
Section: Biomedical Approaches To Diagnose Alleviate or Prevent Joimentioning
confidence: 99%
“…Urinary concentration of PD/DPD ratio was found significantly higher in the OA patients than in the controls. However, the PD/PDP ratio was not associated with any specific clinical or radiological findings [24]. Another bone turnover-resorption-marker CTX-I was assessed in patients with erosive and non-erosive OA of the hands.…”
Section: Resultsmentioning
confidence: 99%
“…Serum NPIIIP was measured by radioimmunoassay using a commercial procollagen III kit (Orion Diagnostica, Espoo, Finland). PYR and D‐PYR were estimated using high‐performance liquid chromatography (HPLC) as described previously 8…”
Section: Methodsmentioning
confidence: 99%